2009
DOI: 10.1088/0268-1242/24/7/075024
|View full text |Cite
|
Sign up to set email alerts
|

Electrical behaviour of Ti-doped Ta2O5on N2O- and NH3-nitrided Si

Abstract: The influence of process parameters: doping approach, Si surface nitridation ambient (NH 3 and N 2 O), type of the gate (Al and W) and its technology of deposition on the electrical characteristics (capacitance-voltage, temperature-dependent current-voltage curves), and the mechanism of conductivity of Ti-doped stacks (6 nm) have been investigated. Among the three factors studied, the surface engineering appears to be with the greatest impact on the film permittivity and stack charges. It is shown that the Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…We now turn our attention to identification of the nature of 0.7 eV deep trap level extracted from the I-V-T characteristics. Similar trap level has been reported in rf-sputtered Ta 2 O 5 (0.6-0.75 eV) [20,27] as well as Ti-doped Ta 2 O 5 (0.62-0.72 eV) [28] and attributed to H-related bond in Ta 2 O 5 [27]. As our samples received standard forming gas annealing in H 2 /N 2 atmosphere, H-related defects throughout the whole gate stack may be responsible for the trap level involved in conduction mechanisms.…”
Section: I-v-t Characteristicssupporting
confidence: 84%
“…We now turn our attention to identification of the nature of 0.7 eV deep trap level extracted from the I-V-T characteristics. Similar trap level has been reported in rf-sputtered Ta 2 O 5 (0.6-0.75 eV) [20,27] as well as Ti-doped Ta 2 O 5 (0.62-0.72 eV) [28] and attributed to H-related bond in Ta 2 O 5 [27]. As our samples received standard forming gas annealing in H 2 /N 2 atmosphere, H-related defects throughout the whole gate stack may be responsible for the trap level involved in conduction mechanisms.…”
Section: I-v-t Characteristicssupporting
confidence: 84%
“…The analysis of the temperature dependence of the current in Ti:Ta 2 O 5 layers [48] reveal that the energy levels of the defects participating in the conduction are in the range of 0.6-0.7 eV and do not depend on the method of Ti incorporation.…”
Section: Ti-doped Ta 2 Omentioning
confidence: 97%
“…Rapid thermal nitridation of the Si surface in NH 3 at 700 • C for 20 s before deposition of high-k layer was done in order to improve the permittivity of the interface layer. Our previous study [33] showed that this nitridation causes an increase of the dielectric constant of the stack and improves its electrical performance through formation of SiON interface layer (with a thickness of 1 nm) instead of SiO 2 -like layer. Using these substrates the following two sets of samples were prepared: MIS capacitors with pure and with lightly Al-doped Ta 2 O 5 , respectively.…”
Section: Methodsmentioning
confidence: 99%